Anticancer Potential of Coumarin and its Derivatives - Bhattarai, Narayan; Kumbhar, Anupa A.; Pokharel, Yuba R.; Yadav, Paras Nath (Mini Reviews in Medicinal Chemistry, 2021)
Coumarins are found in higher plants like Rutaceae and Umbelliferae and essential oils of cinnamon bark, cassia leaf, and lavender oil. Coumarin compounds show different biological properties, viz antimicrobial, antibacterial, antifungal, antioxidant, antitumor, anti-HIV, antihypertension, anticoagulant, anticancer, antiviral, anti-inflammatory, analgesics, antidiabetic, anti-depressive, and other bioactive properties. Coumarin and its derivatives possess anticancer activity against different types of cancers such as prostate, renal, breast, laryngeal, lung, colon, CNS, leukemia, malignant melanoma. In this review, current developments of coumarin-based anticancer agents viz simple coumarin, furanocoumarin, pyranocoumarin, pyrone-substituted coumarin, and their important derivatives have been discussed. The coumarin-triazole, coumarin-chalcone, coumarin-thiosemicarbazone derivatives, and coumarin-metal complexes have been found more potent than coumarin. Hence, further study and structural improvement on coumarin and its derivatives may lead to the design and development of more potent anticancer agents.
Keywords: coumarin-triazole